Bridging the communication gap: How clarity and feedback shape employee understanding and performance - Nonche, Rudiansah; Abd Malek, Marwa (Jurnal Penyelidikan Sains Sosial, 2026)
It is important to practice an effective communication, in order to ensure employee’s engagement, hence, promoting organizational performance. However, many institutions failed to maintain such an effective communication among employees, both upward and downwards. In addition, some staff never get adequate feedback on how they can improve their performance. These leads to poor understanding on their own job and responsibilities, on top of it leading to institution’s poor performance. To detect if this problem occurs at Kolej Komuniti Sandakan, this study was conducted to identify the extent to which communication is effective in terms of information clarity, communication openness, feedback adequacy, and upward and downward communication among college staff. A survey was distributed among 26 Kolej Komuniti Sandakan staff members using a questionnaire adapted from Communication Satisfaction Questionnaire (CSQ). Findings indicated an interesting insight, which staff are receiving such a high clarity of information. However, staff reported low satisfaction on honesty and openness communication among colleagues, as well as low trust among colleague’s interactions. They also reported ineffective communication was given from the top management. Other than that, staff get less information regarding key decisions made by top management. They also get limited guidance on what they should improve. Accordingly, this study suggests the top management to increase transparency, provide constructive feedback and build trust among all staff. A professional development training can be done among staff to enhance communication, such as how to respectfully give and receive feedback objectively. Supervisors need to demonstrate openness, manage sensitive issues confidentially and praise staff’s contributions to motivate. Besides, using suitable platforms for different information especially downward communication is very important. On top of that, providing clear feedback and guidance for poor performance regardless employees’ working experience are important to improve their accountability and engagement.